The Evolution of Galápagos Volcanoes: An Alternative Perspective - Harpp, Karen S.; Geist, Dennis J. (Frontiers in Earth Science, 2018)
The older eastern Galápagos are different in almost every way from the historically active western Galápagos volcanoes. The western Galápagos volcanoes have steep upper slopes and are topped by large calderas, whereas none of the older islands has a caldera, an observation that is supported by recent gravity measurements. Moreover, the eastern islands tend to have been constructed by linear fissure systems and many are cut by faults. Most of the western volcanoes erupt evolved basalts with an exceedingly small range of Mg#, Lan/Smn, and Smn/Ybn. This is attributed to homogenization in a crustal-scale magmatic mush column, which is maintained in a thermochemical steady state, owing to high magma supply directly over the Galápagos mantle plume. The exceptions are volcanoes at the leading edge of the hotspot, which have yet to develop mush columns, and volcanoes that are waning in activity, because they are being carried away from the plume. In contrast, the eastern volcanoes erupt relatively primitive magmas, with a large range in Mg#, Lan/Smn, and Smn/Ybn. This is attributed to isolated, ephemeral magmatic plumbing systems supplied by smaller magmatic fluxes throughout their histories. Consequently, each batch of magma follows an independent course of evolution, owing to the low volume of hypersolidus material beneath these volcanoes. The magmatic flux to Galápagos volcanoes negatively correlates with the distance to the Galápagos Spreading Center (GSC). When the ridge was close to the plume, most of the plume-derived magma was directed to the ridge. Currently, the active volcanoes are much farther from the GSC, thus most of the plume-derived magma erupts on the Nazca Plate and can be focused beneath the large young shields. We define an intermediate sub-province comprising Rabida, Santiago and Pinzon volcanoes, which were most active about 1 Ma. They have all erupted dacites, rhyolites, and trachytes, similar to the dying stage of the western volcanoes, indicating that there was a relatively large volume of mush beneath them. Morphologically, however, they are more like the eastern volcanoes, and have erupted lavas with a large range in composition.